2014
DOI: 10.1063/1.4864651
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of current free double layers in helicon plasmas

Abstract: The paper presents investigations of current free double layer (CFDL) that forms in helicon plasmas. In contrast to the other work reporting on the same subject, in the present investigations the double layer (DL) forms in a mirror-like magnetic field topology. The RF compensated Langmuir probe measurements show multiple DLs, which are in connection with, the abrupt fall of densities along with potential drop of about 24 V and 18 V. The DLs strengths e DV p k T e are about 9.5 and 6, and the corresponding widt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…In order for electron impact excitation of the argon ion ground state to occur and be maintained, there must be a sufficient number of electrons with energy>19.2 eV. The existence of an energetic electron population has been verified in the study of Sahu et al [5,15]. This means that the concentration of energetic electrons drops quickly along the axis direction and becomes very low downstream of the DL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order for electron impact excitation of the argon ion ground state to occur and be maintained, there must be a sufficient number of electrons with energy>19.2 eV. The existence of an energetic electron population has been verified in the study of Sahu et al [5,15]. This means that the concentration of energetic electrons drops quickly along the axis direction and becomes very low downstream of the DL.…”
Section: Resultsmentioning
confidence: 99%
“…Its current-free nature in lowcollisional, magnetically expanding, inductive-or wave-mode discharges distinguishes helicon double layers [12][13][14] from other current-driven double layers. The DL in the plateau region of mirror magnetic field topology was also investigated [5,15]. A large density gradient was used to explain the formation of CFDL [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A neutral beam forms, consisting of a jet of ions and electrons, without need for a neutralizing cathode. CFDLs have been observed to be one of the possible ion acceleration mechanisms [116,117], with ambipolar ion acceleration being the other [118]. It is important to note that, although CFDLs are predicted to produce no thrust [119], experiments have shown that diamagnetic forces in these systems contribute significantly to the thrust [120].…”
Section: Double Layers and Beamsmentioning
confidence: 99%
“…Over the past decade, the physical mechanisms of the thrust generation in the magnetic nozzle plasma thrusters have been investigated by theoretical models [7][8][9], numerical calculations [10], and laboratory experiments [11][12][13][14]. A number of experiments have shown spontaneous ion accelerations due to formations of a current-free double layer and an ambipolar electric field in the magnetically expanding plasmas [15][16][17][18]; subsequent Fruchtman's one-dimensional model has shown that the spontaneous electric field does not impart a momentum to the plasma, while the axial plasma momentum increases along the magnetic nozzle [7], which was followed by some two-dimensional models [19,20]. Individual measurements of the force components exerted to the source tube and the magnetic fields have confirmed the role of the magnetic nozzle [21], where the model analyzed by Takahashi et al has shown that the thrust increased by the magnetic nozzle corresponds to a Lorentz force due to an electron diamagnetic drift current and a radial magnetic field, which has been further investigated more recently in detail [22].…”
mentioning
confidence: 99%